Inflation in times of overlapping emergencies: Systemically significant prices from an input-output perspective - Isabella Weber; Jesus Lara Jauregui; Lucas Teixeira; Luiza Nassif Pires (University of Massachusetts, Department of Economics, 2022)
In the overlapping global emergencies of the pandemic, climate change and geopolitical confrontations, supply shocks have become frequent and inflation has returned. This raises the question how sector-specific shocks are related to overall price stability. This paper simulates price shocks in an input-output model to identify sectors which present systemic vulnerabilities for monetary stability in the US. We call these prices systemically significant. We find that in our simulations the pre-pandemic average price volatilities and the price shocks in the COVID-19 and Ukraine war inflation yield an almost identical set of systemically significant prices. The sectors with systemically significant prices fall into three groups: energy, basic production inputs other than energy, basic necessities, and commercial and financial infrastructure. Specifically, they are "Petroleum and coal products", "Oil and gas extraction", "Utilities", "Chemical products", "Farms", "Food and beverage and tobacco products", "Housing", and "Wholesale trade". We argue that in times of overlapping emergencies, economic stabilization needs to go beyond monetary policy and requires institutions and policies that can target these systemically significant sectors.
Keywords: C67; E31; E61; 330; Inflation; Systematically significant prices; Input-output analysis; Cost-push price formation